PENINGKATAN AKTIVITAS BELAJAR MATEMATIKA SISWA KELAS XII TKR SMK ADZKIA PADANG DENGAN MODEL STAD (JURNAL LEMMA, 2015)
The implementation process of mathematics learning in schools often experience   many obstacles. One of them is the  low activity of students to learn. This phenomenon is visible at the time of the teaching-learning process. The  students tend to chat with their friend during the  process. Moreover, they often ask permission out. These behaviors show the lack of students desire to learn. It will affect the students  understanding about  the  subject  matter.  Resulting  in  student  participation in  mathematics learning is low. To help improve the quality of education, effort required of teachers in improving students' activity in teaching and learning. This study aims to explain the process of improving activity of mathematics learning and describes how high achievement activities in the class XII TKR SMK Padang Adzkia STAD model. The research is classroom action research conducted in two cycles. Data collection techniques drawn from the charging sheets observation by the observer. Technique of data analysis used alur model. This technique consists or 3 alur; data reduction,  data  of the description, and transformation raw data which  comes from field note. The data analysis used is descriptive analysis. The results showed that an increase in activities. Activities student successfully improved from all the observed indicators of the cycle I to the end of cycle II. One of factors causes improving activity achievement by using STAD model is cooperative between group member to understand the material. It can be concluded that the implementation of STAD model to increase activities mathematics learning